A turbo-taxonomic study of Thai Aleiodes (Aleiodes) and Aleiodes (Arcaleiodes) (Hymenoptera: Braconidae: Rogadinae) based largely on COI barcoded specimens, with rapid descriptions of 179 new species - Butcher, Buntika Areekul; Smith, M. Alex; Sharkey, Mike J.; Quicke, Donald L. J. (Zootaxa, 2012)
The Aleiodes (Aleiodes) and Aleiodes (Arcaleiodes) species of Thailand are revised based on extensive recent collectingas well as existing museum material, and combining evidence from DNA barcoding (5’ end of mitochondral cytochromeoxidase 1) for sequenced material with species known from morphological data alone. The approach taken (here termed‘turbo-taxonomy’) has been to rely heavily on colour light microscopy photographic illustration, with brief descriptionscontributing principally to characters that are not apparent from the micrographs. All new species are attributed to Quicke& Butcher. Although the very high level of diversity of the Thai fauna means this is necessarily preliminary, in the sensethat there are undoubtedly many more species awaiting to be described, it is the first reasonably comprehensive study ofa tropical Aleiodes fauna. One hundred and seventy six new species of the subgenus Aleiodes (viz. Aleiodes achingae sp.nov., Aleiodes aciculodeum sp. nov., Aleiodes adorabelleae sp. nov., Aleiodes agagg sp. nov., Aleiodes alboluteus sp.nov., Aleiodes anguaae sp. nov., Aleiodes angulodeum sp. nov., Aleiodes antescutum sp. nov., Aleiodes apiconigrus sp.nov., Aleiodes archicolorus sp. nov., Aleiodes areelucki sp. nov., Aleiodes ascrobi sp. nov., Aleiodes asperum sp. nov.,Aleiodes atuin sp. nov., Aleiodes bachmaduplus sp. nov., Aleiodes bachmatriplus sp. nov., Aleiodes basipunctatus sp.nov., Aleiodes basistriatus sp. nov., Aleioides binkyi sp. nov., Aleiodes biscutus sp. nov., Aleiodes bobwhartoni sp. nov.,Aleiodes brevimedius sp. nov., Aleiodes brunniguttatus sp. nov., Aleiodes butcheri sp. nov., Aleiodes buzuriduplus sp.nov., Aleiodes buzuriquadruplus sp. nov., Aleiodes buzuritriplus sp. nov., Aleiodes calicis sp. nov., Aleiodes calvus sp.nov., Aleiodes canus sp. nov., Aleiodes caprinus sp. nov., Aleiodes castaneus sp. nov., Aleiodes centralis sp. nov.,Aleiodes chamba sp. nov., Aleiodes chenduplus sp. nov., Aleiodes cheni sp. nov., Aleiodes codon sp. nov., Aleiodescomplexus sp. nov., Aleiodes concoronarius sp. nov., Aleiodes conina sp. nov., Aleiodes connudatum sp. nov., Aleiodesconpectenus sp. nov., Aleiodes constriatum sp. nov., Aleiodes contemptus sp. nov., Aleiodes coronopus sp. nov., Aleiodescorrusciput sp. nov., Aleiodes cramum sp. nov., Aleiodes curtivena sp. nov., Aleiodes curvicauda sp. nov., Aleiodesdamus sp. nov., Aleiodes darlingtonia sp. nov., Aleiodes deathi sp. nov., Aleiodes definus sp. nov., Aleiodes deyoyoi sp.nov., Aleiodes dimorphus sp. nov., Aleiodes divergerus sp. nov., Aleiodes downeyi sp. nov., Aleiodes eadyi sp. nov.,Aleiodes elongatus sp. nov., Aleiodes etvalinus sp. nov., Aleiodes faciei sp. nov., Aleiodes flannelfooti sp. nov., Aleiodesflavostriatus sp. nov., Aleiodes fovodeum sp. nov., Aleiodes fuscomedius sp. nov., Aleiodes gaga sp. nov., Aleiodesgaspodei sp. nov., Aleiodes georgiae sp. nov., Aleiodes glabribasalis sp. nov., Aleiodes globofemurus sp. nov., Aleiodesglutinum sp. nov., Aleiodes griseimaculatus sp. nov., Aleiodes guidaae sp. nov., Aleiodes hei sp. nov., Aleiodeshelenhippersonsae sp. nov., Aleiodes herrena sp. nov., Aleiodes hircus sp. nov., Aleiodes incisus sp. nov., Aleiodesjimwhitfieldi sp. nov., Aleiodes kitchingi sp. nov., Aleiodes klopfsteinae sp. nov., Aleiodes lavaeolous sp. nov., Aleiodeslemniscus sp. nov., Aleiodes liessa sp. nov., Aleiodes lipwigduplicitus sp. nov., Aleiodes lipwigi sp. nov., Aleiodeslobocarinus sp. nov., Aleiodes longivena sp. nov., Aleiodes macroophthalmus sp. nov., Aleiodes maculiput sp. nov.,Aleiodes magratae sp. nov., Aleiodes malarius sp. nov., Aleiodes malichi sp. nov., Aleiodes mediofuscus sp. nov.,Aleiodes mediomaculatus sp. nov., Aleiodes megaophthalmos sp. nov., Aleiodes mellificus sp. nov., Aleiodes mericeti sp.nov., Aleiodes microophthalmos sp. nov., Aleiodes molecryptus sp. nov., Aleiodes morti sp. nov., Aleiodes mutilus sp.nov., Aleiodes nathismus sp. nov., Aleiodes necsubson sp. nov., Aleiodes niveni sp. nov., Aleiodes nivori sp. nov.,Aleiodes nonicones sp. nov., Aleiodes occimaculatus sp. nov., Aleiodes opus sp. nov., Aleiodes orion sp. nov., Aleiodespaenicarinus sp. nov., Aleiodes pallimedius sp. nov., Aleiodes palmae sp. nov., Aleiodes palmatipes sp. nov., Aleiodesparabuzurae sp. nov., Aleiodes parasongsi sp. nov., Aleiodes parisaae sp. nov., Aleiodes paulmarshi sp. nov., Aleiodespectopulicis sp. nov., Aleiodes pectunguis sp. nov., Aleiodes pectunguisella sp. nov., Aleiodes penultimoluteus sp. nov.,Aleiodes phantasmatis sp. nov., Aleiodes pinnulae sp. nov., Aleiodes placidus sp. nov., Aleiodes polititergus sp. nov.,Aleiodes ponderi sp. nov., Aleiodes postmaculus sp. nov., Aleiodes prillae sp. nov., Aleiodes probuzurae sp. nov.,Aleiodes procarinatus sp. nov., Aleiodes procoronarius sp. nov., Aleiodes pronopus sp. nov., Aleiodes propodealis sp.nov., Aleiodes propodocarinus sp. nov., Aleiodes protocastaneus sp. nov., Aleiodes pseudicones sp. nov., Aleiodespteppicymoni sp. nov., Aleiodes ptraci sp. nov., Aleiodes rectanguliguttatus sp. nov., Aleiodes reticulisoma sp. nov.,Aleiodes reus sp. nov., Aleiodes ridcullyi sp. nov., Aleiodes rincewindi sp. nov., Aleiodes risaae sp. nov., Aleiodes rivulussp. nov., Aleiodes rufomedius sp. nov., Aleiodes rugoscutus sp. nov., Aleiodes sacharissa sp. nov., Aleiodes scottshawisp. nov., Aleiodes selachiii sp. nov., Aleiodes sesquipunctatus sp. nov., Aleiodes similicodon sp. nov., Aleiodes songsi sp.nov., Aleiodes sophieae sp. nov., Aleiodes stibbonsi sp. nov., Aleiodes stohelit sp. nov., Aleiodes subemarginatus sp. nov.,Aleiodes subfuscomedius sp. nov., Aleiodes submediofuscus sp. nov., Aleiodes subson sp. nov., Aleiodes sutthisani sp.nov., Aleiodes synorion sp. nov., Aleiodes teatimei sp. nov., Aleiodes tetrarugulosus sp. nov., Aleiodes thirakupti sp. nov.,Aleiodes tmaliaae sp. nov., Aleiodes tobiasi sp. nov., Aleiodes transvena sp. nov., Aleiodes tricoloripes sp. nov., Aleiodestrisphaeropyx sp. nov., Aleiodes tulipus sp. nov., Aleiodes turgidipalpus sp. nov., Aleiodes valinus sp. nov., Aleiodesvariifemurus sp. nov., Aleiodes vetinarii sp. nov., Aleiodes vietuput sp. nov., Aleiodes yalaensis sp. nov. and Aleiodeszuburae sp. nov., and three of the subgenus Arcaleiodes (viz. Aleiodes dresdeni sp. nov., Aleiodes (Arcaleiodes)vanachterbergi sp. nov. and Aleiodes (Arcaleiodes) siamensis sp. nov.) are described as new. An illustrated identificationkey provided, and some novel and hardly used characters are discussed and illustrated. Morphological and molecularcomparison of these species with the better-known Holarctic fauna shows that several previously unrecognised speciesgroups may be distinguished. Based on the Chao 1 diversity estimator, which additionally takes into account the numberof specimens represented by precisely one, and the number represented by precisely two individuals, it is estimated that when fully known, the Thai fauna includes at least 438 species of Aleiodes.